ANALISIS BIBLIOMETRIK: PENELITIAN PEMBELAJARAN BERBASIS DIGITAL DALAM PENDIDIKAN AGAMA ISLAM (PAI) - Harif Rahman Suyatno; Dipalpa Rego; Martin Kustati; Bashori (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to map the development, trends, and research focus related to digital-based learning in Islamic Education (PAI) through a bibliometric approach. The main problem underlying this research is the absence of a comprehensive overview of publication trends and researchers’ contributions in the field of PAI digitalization. This study employs a bibliometric method by analyzing article metadata obtained from the Scopus database within the 2021–2025 timeframe. The data were analyzed using quantitative descriptive techniques and network visualization with VOSviewer to identify keyword co-occurrence patterns, author collaboration, and research topic clusters. The results show a significant increase in publications related to digital learning in PAI in 2025, particularly in themes such as e-learning, interactive media, and mobile learning. The most dominant keywords include “Islamic education,” “digital learning,” and “e-learning.” Furthermore, the study identified research clusters focusing on digital media development, technology integration in PAI learning, and pedagogical innovations based on online platforms. These findings provide a scientific mapping that can serve as a foundation for future research development as well as more adaptive PAI learning practices aligned with the advancement of digital technologies.